Pectin Films with Recovered Sunflower Waxes Produced by Electrospraying - Mayra C. Chalapud; Erica R. Baümler; Amalia A. Carelli; Ma. de la Paz Salgado-Cruz; Eduardo Morales-Sánchez; Minerva Rentería-Ortega; Georgina Calderón-Domínguez (Membranes, 2022)
Valorization of by-products obtained from food processing has achieved an important environmental impact. In this research, sunflower wax recovered from oil refining process was incorporated to low and high-methoxyl pectin films produced by electrospraying. Film-forming solutions and wax-added electrosprayed films were physical and structurally evaluated. The addition of sunflower wax to the film-forming solutions reduces conductivity while raising surface tension and density, whereas the type of pectin had a larger impact on viscosity, with the low-methoxyl solution having the highest value. These changes in physical solution properties influenced the film characteristics, observing thicker films with lower water vapor transmission rate (WVTR) when adding wax. Micrographs obtained by scanning electron microscopy (SEM) revealed the presence of wax particles as small spherical shapes, having a good distribution through the sectional area of films. According to X-ray diffraction (XRD), atomic force microscopy (AFM) and mechanical properties analyses, the presence of wax had an impact on the degree of crystallinity, producing a more amorphous and rougher film’s structure, without affecting the elongation percentage and the tensile stress (p>0.05). These results showed that wax addition improves the physical properties of films, while the suitability of using both pectins and the electrospraying technique was demonstrated.